A Case of Rupioid Syphilis Masquerading as Aggressive Cutaneous Lymphoma - Jonathan Braue; Thomas Hagele; Abraham Tareq Yacoub; Suganya Mannivanan; Frank Glass; Lubomir Sokol; John Norman Greene (Mediterranean Journal of Hematology and Infectious Diseases)
Secondary syphilis has been known since the late 19th century as the great imitator; however, some experts now regard cutaneous lymphoma as the great imitator of skin disease. Either disease, at times an equally fastidious diagnosis, has reported to even mimic each other. It is thus vital to consider these possibilities when presented with a patient demonstrating peculiar skin lesions. No other manifestation of secondary syphilis may pose such quandary as a rare case of rupioid syphilis impersonating cutaneous lymphoma. We present such a case, of a 36-year-old HIV positive male, misdiagnosed with aggressive cutaneous lymphoma, actually exhibiting rupioid syphilis thought secondary to immune reconstitution inflammatory syndrome (IRIS).